Caracterização nutricional de genótipos de feijão-caupi com potencial de uso na biofortificação - Silva, Ana Beatriz Machado da (2023)
The nutritional composition of cowpea (Vigna unguiculata L. Walp.) seeds has been the subject of studies since research indicates the variability between genotypes for nutrients that are important for human nutrition, enabling, through genetic improvement, obtaining biofortified cultivars. It emphasizes the importance of providing enriched or biofortified foods, not only for the food industry but also to improve the quality of food and nutrition for the population. Thus, the objective of this work was to evaluate the nutritional potential of cowpea genotypes with potential use in biofortification. For that, 43 genotypes from the Active Germplasm Bank of the Federal University of Ceará (UFC) were evaluated, which underwent centesimal and mineral analysis, and from these eight genotypes were chosen that stood out in the ranking of the Nutritional Quality Index (IQN1). The eight selected genotypes and two controls (BRS Tumucumaque and BRS Juruá) were carried out in a field experiment. After harvesting the immature grains, chemical analyzes were carried out: centesimal, nutritional and Nuclear Magnetic Resonance (NMR) to identify the chemical compounds of each genotype studied. The genotype CE-0685 had the highest content of P, Mg and Fe minerals, while the genotypes CE-0024 and CE-0097 had the highest levels of Na and a reduction in the levels of all other nutrients. The genotypes CE-0796, CE-0024 and CE-0685 have the highest levels of sucrose and stachyose, verbascose and raffinose (oligosaccharides). On the other hand, the genotypes CE-1002, BRS Juruá and CE-0978 showed the highest levels of amino acids such as valine, leucine, phenylalanine, tyrosine, carbohydrates such as α-glucose and β-glucose, in addition to phenolics such as trigonelline, among others such as acetic acid, fumaric acid, acetylcholine and uracil. The NMR result indicates that cowpea contains a high level of aliphatic, carbohydrate and aromatic compounds. The main compounds detected were carbohydrates and amino acids. The genotypes CE-0796, CE-1002, CE-0685 and BRS Juruá have nutritional potential for the consumption of green grains.